Intracranial Hemorrhage In Patients Receiving Direct Oral Anticoagulant Therapy: Clinical Assessment, Management And Related Laboratory Studies. (28th October 2020) - Xie, M; Wyrzykowski, M
Abstract: Introduction/Objective: Direct oral anticoagulants (DOACs) have gained wide use in prevention and treatment of thromboembolic diseases. Although relatively rare with DOAC therapy, intracranial hemorrhage may become a medical emergency and needs to be managed with caution to avoid adverse consequences. Methods: During the review of 94 patients with DOAC therapy related bleeding complications at William Beaumont hospital – Troy, Michigan, 3 patients were identified with intracranial hemorrhage. Information on DOAC therapy, the cause related to intracranial hemorrhage, and clinical assessment and management of these patients were collected from electronic medical charts with concurrent laboratory studies. Results: There were 1 male and 2 female patients, ages 63, 67 and 86. Two patients were taking rivaroxaban 20 mg daily and 1 patient apixaban 5 mg bid for atrial fibrillation and DVT. Patients were clinically stable with no prior significant bleeding events, except for minor skin rashes. All patients experienced a minor trauma to the head and showed signs of brain injury. They were brought to the emergency department immediately. DOAC therapy was discontinued during the emergency evaluation. CT studies revealed 1 patient with subdural hematoma and 2 patients with focal intraparenchymal hemorrhage without mass effects. Both clinical and laboratory assessment revealed stable medical conditions. Patients received conservative care without surgical intervention and repeat CT studies demonstrated resolution of hemorrhage. One patient discontinued DOAC therapy permanently and the others resumed DOAC therapy with antidotes available. Clinical follow up showed no additional bleeding events. Conclusion: Intracranial hemorrhage can occur in patients received DOAC therapy, even in clinically stable patients, and most likely happens after head injury. In this small group of patients, both clinical and laboratory evaluations showed stable medical conditions, with no need for surgery intervention. However, the decision of continuing DOAC therapy should be made with caution and it is reasonable to have antidote available for these patients.